Surface-enhanced infrared absorption spectroscopy and electrochemistry reveal the impact of nanoparticles on the function of protein immobilized on mimic biointerface. (1st September 2016) - Zhang, Xiaofei; Zeng, Li; Liu, Li; Ma, Zhifang; Jiang, Xiue
Abstract: Study of the interactions between engineered nanoparticles and biomolecules plays an important role in understanding nano-bio effect. However, most of studies focus on the interaction of protein with nanoparticle in bulk phase, the impact of nanoparticle on the function of protein immobilized on the biological interface has been ignored for a long time. In this paper, we study the effect of SiO2 NPs on electron transfer function of cytochrome c (cyt c ) adsorbed onto the 11-mercaptoundecanoic acid (MUA) self-assembled monolayer (SAM) by surface-enhanced infrared absorption spectroscopy (SEIRAS) combined with electrochemistry. Our results disclose that instead of inhibiting the electron transfer, exposure of SiO2 NPs enhances the redox reversibility, electron transfer rate, and catalytic performance of adsorbed cyt c, but induces a slight negative shift in the formal potential of the adsorbed cyt c . Interaction of SiO2 NPs slightly induces the structural changes of the β-sheet in the oxidized form and the change of microenvironment surrounding them, which could further change the microenvironment and the orientation of heme, facilitating the hydration of cyt c at the oxidized state. It could be the enhanced hydration of cyt c (Fe 3+ ) and a smaller change in the total hydration from reduced to oxidized state that results in the slight negative shift in the formal potential and promotes the electron transfer capability. Besides, cyt c 's slight conformational change and the disturbance to the microenvironment of heme resulting from the adsorption of SiO2 NPs could also be one of the reason that leads to the enhanced catalytic capability towards the reduction of H2 O2 .